Electrochemical Aromatization of Dihydroazines: Effect of Chalcogenophosphoryl (CGP) Substituents on Anodic Oxidation of 9-CGP-9,10-dihydroacridine - Shchepochkin, Alexander V.; Chupakhin, Oleg N.; Demina, Nadezhda S.; Averkov, Maxim A.; Shimanovskaya, Tatyana Yu.; Slepukhin, Pavel A.; Volkov, Pavel A.; Telezhkin, Anton A.; Trofimov, Boris A.; Charushin, Valery N. (Synthesis, 2021)
The effect of chalcogenophosphoryl fragments on the anodic oxidation of 9-chalcogenophosphoryl-9,10-dihydroacridines was studied in detail. The data of X-ray structural analyses, quantum chemical calculations, and cyclic voltammetry measurements obtained for these compounds provide an explanation of the observed features. The direct electrochemical phosphorylation of acridine was first carried out successfully.
Keywords: electrochemical phosphorylation; anodic oxidation; C–H functionalization; green chemistry; acridine